Satuan Pendidikan Aman Bencana (SPAB) Berbasis Partisipatory Rural Appraisal di Madrasah Aliyah Sunan Santri Lamongan - Kiki Septaria; Atika Fatharani; Binar Ayu Dewanti; Zia Retno Utami (TAAWUN, 2024)
The goal of this activity is to create a disaster-safe school environment at MA Sunan Santri Lamongan and to familiarize the school community with disaster preparedness. The methods used in this activity include training based on Participatory Rural Appraisal and an experimental method implementing a one-group pre-test post-test design to assess the impact of the implemented training. The results of this activity have shown an increase in students' understanding and skills in disaster preparedness. Furthermore, the program has demonstrated that each series of activities enhances the disaster mitigation skills of the school community. The SPAB program at MA Sunan Santri Lamongan enhances disaster awareness and preparedness among students and staff, creating a safer and more responsive school environment. This program also strengthens the disaster mitigation skills of the school community, ensuring a quick and effective response to potential future disasters.